Behavior of Hydrated Lipid Bilayers at Cryogenic Temperatures - Meineke, Jakob; Weik, Martin; Zaccai, Giuseppe; Fragneto, Giovanna (Frontiers in Chemistry, 2020)
Neutron diffraction was used to study the behavior of water present in phospholipid multilamellar stacks from 1,2-dimyristoyl-sn-glycero-3-phosphatidylcholine (DMPC) at cryogenic temperatures. Evidence was found for the existence of a highly viscous phase of water that exists between 180 and 220 K based on the observation that water can leave the intermembrane space at these low temperatures. Similar measurements are described in the literature for purple membrane (PM) samples. From a comparison with results from this natural membrane by using the same flash-cooling protocol, it is found that in the case of pure lipid samples, less water is trapped and the water flows out at lower temperatures. This suggests that the water is less hindered in its movements than in the PM case. It is shown that at least the Lβ′-phase of DMPC can be trapped likely by flash cooling; upon heating to about 260 K, it transforms to another phase that was not fully characterized.